Efektifitas Acceptance and Commitment Therapy (ACT) dalam Menurunkan Tingkat Kecemasan Pada Pasien Pengidap Gagal Ginjal Kronis: Penelitian - Rahmawati, Ida; Wahyudi, Hedi; Suhana, Suhana (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Chronic kidney disease (CKD) patients undergoing hemodialysis are at high risk of experiencing anxiety due to lifestyle changes, dependence on dialysis machines, uncertainty of prognosis, and fear of death. If left untreated, anxiety can worsen the patient's physical and mental condition. Various psychological interventions have been used, but many are ineffective or difficult to implement in chronic patients. This study aims to determine the effectiveness of Acceptance and Commitment Therapy (ACT) in reducing anxiety in CKD patients. The method used was a quasi-experimental with a one-group pre-post test design, involving 6 participants through purposive sampling. Anxiety was measured using the Beck Anxiety Inventory (BAI) by Dr. Aaron T. Beck (21 items). Data analysis was performed using the Paired T-test and the N-Gain test. The results showed that ACT significantly reduced anxiety (p = 0.000 < 0.05) with an average N-Gain of 57.36% (categorized as quite effective). Thus, ACT is quite effective in reducing anxiety in CKD patients at Hospital X, City B, Central Kalimantan.